Hepatic Mucormycosis Mimicking Veno-Occlusive Disease: Report of a Case and Review of the Literature. (March 2016) - Yang, Chen; Friess, Stuart H.; Dehner, Louis P.
The clinical history of a 12-year-old boy with trisomy 21 who suffered from relapsed pre–B cell acute lymphocytic leukemia with clinical symptoms of hepatic veno-occlusive disease and death is reported. The postmortem findings were significant for hepatic mucormycosis with selective involvement of the central veins, sinusoids, and portal tracts resulting in obstruction of the outflow tract and massive hepatocellular necrosis. Hematogenous dissemination of mucormycosis causing acute splenitis and hemorrhagic intestinal necrosis were also observed. To our knowledge, mucormycosis invasion of the central veins, sinusoids, and portal tracts by fungal hyphae resulting in a syndrome mimicking hepatic veno-occlusive disease has not been previously reported.